Perceções sobre o regime legal das drogas e influências normativas nos consumos de drogas - Helena de Fátima Ferreira Antunes (2013)
Throughout this study we seek to understand, in depth and detail, the perceptions about the legal framework of drugs and normative influences in the use of drugs, through two contrasting groups - a group of drug addicts and a group of non-consumers of illicit drugs - using for that effect, qualitative methodologies. Data was collected through semi-structured interviews to 16 subjects (8 subjects of each group). The results indicate that the two contrasting groups present themselves, generally favourable to the interdiction of drug use, and the drug addicts group believes that drug use should be classified within a legal framework of infringement, opposing to the group of non-consumers that are favourable to the consumption as a crime.